Corporate Financial Reporting and Taxes: How Important Is Prior Performance? - Lukas Timbate; Dereje Asrat (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- How do firms behave after significantly missing or exceeding analysts' earnings estimates in terms of managing earnings and avoiding taxes? Motivation- Prior research provides strong evidence suggesting that managers are motivated to perform at or above analysts' expectations and steer earnings higher to prevent unpleasant earnings surprises. Prior studies have also documented that firms are likely to manage their earnings when they are close to meeting or missing analysts' expectations. However, little is known about how firms behave after either substantially missing or beating analyst earnings estimates. Idea- This study provides evidence on firms' earnings management and tax avoidance activities subsequent to the year in which firms substantially fail or succeed meeting analysts' earnings consensus forecasts. Data- The data were collected from a sample of South Korean firms listed on the Korean Composite Stock Price Index for the years between 2013 and 2020. Tools- Multiple panel data regressions and robustness tests were conducted. Propensity score matching is also used to minimize endogeneity related problems. Findings- Firms are more likely to manage their earnings upward subsequent to significantly missing analysts' expectations. However, their tendency to avoid taxes is lower. Contribution- Little has been explored on how firms significantly missing analysts' expectations could behave in the subsequent period. The findings reported in this study have important implications for regulators, investors, and auditors. This research is also different from most prior related studies in terms of its setting.
Keywords: M40; M41; M48; 650; Analysts' expectations; consensus estimates; earnings forecast; earnings management; financial performance; tax avoidance